2019
DOI: 10.1212/wnl.0000000000006685
|View full text |Cite
|
Sign up to set email alerts
|

Education Research: Electronic patient portal enrollment and no-show rates within a neurology resident clinic

Abstract: ObjectiveTo identify factors that affect appointment adherence and investigate the association of electronic patient portal (ePP) enrollment and patient adherence rates to appointments in the Neurology Resident Clinic (NRC).MethodsPatients scheduled for an appointment during the months of October 2015, February 2016, and June 2016 in the NRC were included. ePP enrollment, date of clinic appointment, method of referral to the clinic, and key demographic criteria were collected. χ2 tests were performed to assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The incidence of T‐tube‐related complications, including T‐tube obstruction/biliary tract infection and related skin issues, was significantly lower in the TCP group, indicating a positive impact of the TCP on clinical prognosis. In addition, the rate of scheduled clinic visits was higher in the TCP group, indicating that the TCP is effective in enhancing patient compliance and enabling patients to cooperate better and provide feedback on treatment (Shah et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of T‐tube‐related complications, including T‐tube obstruction/biliary tract infection and related skin issues, was significantly lower in the TCP group, indicating a positive impact of the TCP on clinical prognosis. In addition, the rate of scheduled clinic visits was higher in the TCP group, indicating that the TCP is effective in enhancing patient compliance and enabling patients to cooperate better and provide feedback on treatment (Shah et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The health system perspective was explored by 15 peer-reviewed [45,48,49,59,65,[69][70][71][128][129][130][131][132][133][134]] and 3 gray literature [106,109,135] studies, which focused on the impact of patient portals on the potential for reducing costs. The studies varied in data collection approaches (prospective observational, n=4; retrospective observational, n=9; survey methods, n=2; and mixed methods, n=3), and the evaluated portal components (portal in general, n=11; viewing laboratory results, n=1; OpenNotes, n=1; secure messaging, n=4; appointments, n=2; and care plan, n=1).…”
Section: Health System Perspective (Reduced Per Capita Cost Of Health Care)mentioning
confidence: 99%
“…Studies evaluating the possible impact of patient portals on no-show appointments compared the pre-post no-show appointment rates and established that portal users had a lower rate of no-show appointments compared with nonusers; however, there was no difference in appointment cancellation rates [48,69,70,129,130]. Mendel et al [130] found portal enrollment increased once the clinic staff promoted the portal as a tool for appointment reminders, which was also associated with increased patient satisfaction [130].…”
Section: Decrease In No-show Appointmentsmentioning
confidence: 99%
See 1 more Smart Citation